A Hierarchy of Cues Directs the Foraging of Pieris rapae (Lepidoptera: Pieridae) Larvae. Issue 6 (27th August 2018) - Tsuji, Jun; Logan, Tiffany; Russo, Ashley
Abstract: The foraging patterns of insects reflect a combination of biotic and abiotic constraints. Pieris rapae (L.) (Lepidoptera: Pieridae) larvae exhibit plasticity in their foraging behavior, and their movements in response to flowers, young foliage, light, and gravity were studied. As predicted for palatable cryptic larvae, young instars of P. rapae exhibited predator avoidance behaviors. First- and second-instar larvae fed underneath the leaves where their eggs were oviposited, while late second- and third-instar larvae migrated away from their feeding damage. Using taxis experiments and choice tests, the direction of larval movement was significantly influenced by a hierarchy of three cues. Third-instar larvae exhibited negative gravitaxis, which could be supplanted by positive trophotaxis to young leaves and flowers. The larvae exhibited a significantly greater attraction to the inflorescence than to young foliage. For both the inflorescence and young foliage, visual cues were sufficient to direct larval movement. Understanding the cues that guide larval foraging may lead to more efficient trap crops for pest management.